Pivotal roles of melanopsin containing retinal ganglion cells in pupillary light reflex in photopic conditions - Bohl, Jeremy Matthew; Hassan, Abdul Rhman; Sharpe, Zachary J.; Kola, Megi; Shehu, Angela; Beaudoin, Deborah Langrill; Ichinose, Tomomi (Frontiers in Cellular Neuroscience, 2025)
The pupillary light reflex (PLR) is crucial for protecting the retina from excess light. The intrinsically photosensitive retinal ganglion cells (ipRGCs) in the retina are neurons that are critical to generating the PLR, receiving rod/cone photoreceptor signals and directly sensing light through melanopsin. Previous studies have investigated the roles of photoreceptors and ipRGCs in PLR using genetically-modified mouse models. Herein, we acutely ablated photoreceptors using N-nitroso-N-methylurea (MNU) to examine the roles of ipRGCs in the PLR. We conducted PLR and multiple electrode array (MEA) recordings evoked by three levels of light stimuli before and 5 days after MNU intraperitoneal (i.p..) injection using C57BL6/J wildtype (WT) mice. We also conducted these measurements using the rod & cone dysfunctional mice (Gnat1–/– & Cnga3–/–:dKO) to compare the results to published studies in which mutant mice were used to show the role of photoreceptors and ipRGCs in PLR. PLR pupil constriction increased as the light stimulus intensified in WT mice. In MNU mice, PLR was not induced by the low light stimulus, suggesting that photoreceptors induced the PLR at this light intensity. By contrast, the high light stimulus fully induced PLR, similar to the response in WT mice. In dKO mice, no PLR was evoked by the low-light stimulus and a slow-onset PLR was evoked by the high-light stimulus, consistent with previous reports. Ex vivo MEA recording in the MNU tissue revealed a population of ipRGCs with a fast onset and peak time, suggesting that they drove the fast PLR response. These results suggest that ipRGCs primarily contribute to the PLR at a high light intensity, which does not agree with the previous results shown by mutant mouse models. Our results indicate that the melanopsin response in ipRGCs generate fast and robust PLR when induced by high light.